The Epistemology Of Siyasah Studies In The Philosophy Of UIN Alauddin Makassar Scientific Trains - Kurniati, Kurniati; Rahmiati, Rahmiati (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2021)
The process of developing a scientific train philosophy is a human problem considering its position as a new scientific philosophy and requires a strong epistemological construct in terms of its source, structure, method and validity. The presence of a new scientific philosophy in the UIN Alauddin Makassar environment as a development of the scientific philosophy of the house of civilization, of course has consequences for tridharma activities including the epistemology of siyasah Syar'iah studies. To answer this problem, this study applies a descriptive-analytical qualitative research model using a multidisciplinary approach. The results showed that the study epistemology of Siyasah Syar'iyah in the UIN Alauddin Makassar environment from the source of the study had been developed by combining various normative bases in line with the vision and mission concept as a faculty and program study and supported by a curriculum of practical elaboration of the vision and mission. In line with that, the paradigm of Siyasah Syar’iyah study in the spectrum of scientific train philosophy places the study of siyasah syariyah to be more inclusive and is required to accommodate various sources, structures, methods and validity of syariyah syariyah that are relevant and constructed.Keywords: Epistemology; Siyasah Syar'iyah; Scientific Train.